COVID-19 Outbreak Related to PM10, PM2.5, Air Temperature and Relative Humidity in Ahvaz, Iran - Yusef Omidi Khaniabadi; Pierre Sicard; Bahram Dehghan; Hassan Mousavi; Saeid Saeidimehr; Mohammad Heidari Farsani; Sadegh Moghimi Monfared; Heydar Maleki; Hojat Moghadam; Pouran Moulaei Birgani (Dr. Sulaiman Al Habib Medical Journal)
In this study, we assessed several points related to the incidence of COVID-19 between March 2020 and March 2021 in the Petroleum Hospital of Ahvaz (Iran) by analyzing COVID-19 data from patients referred to the hospital. We found that 57.5% of infected referrals were male, 61.7% of deaths by COVID-19 occurred in subjects over 65 years of age, and only 2.4% of deaths occurred in younger subjects (> 30 years old). Analysis showed that mean PM10 and PM2.5 concentrations were correlated to the incidence of COVID-19 (r = 0.547, P < 0.05, and r = 0.609, P < 0.05, respectively) and positive chest CT scans (r = 0.597, P < 0.05, and r = 0.541, P < 0.05 respectively). We observed that a high daily air temperature (30–51 °C) and a high relative humidity (60–97%) led to a significant reduction in the daily incidence of COVID-19. The highest number of positive chest CT scans were obtained in June 2020 and March 2021 for daily air temperature ranging from 38 °C and 49 °C and 11 °C and 15 °C, respectively. A negative correlation was detected between COVID-19 cases and air temperature (r = − 0.320, P < 0.05) and relative humidity (r = − 0.384, P < 0.05). In Ahvaz, a daily air temperature of 10–28 °C and relative humidity of 19–40% are suitable for the spread of coronavirus. The highest correlation with the number of COVID-19 cases was found at lag3 (r = 0.42) and at lag0 with a positive chest CT scan (r = 0.56). For air temperature and relative humidity, the highest correlations were found at day 0 (lag0). During lockdown (22 March to 21 April 2020), a reduction was observed for PM10 (29.6%), PM2.5 (36.9%) and the Air Quality Index (33.3%) when compared to the previous month. During the pandemic period (2020–2021), the annual mean concentrations of PM10 (27.3%) and PM2.5 (17.8%) were reduced compared to the 2015–2019 period.